PERAN DANA DESA TERHADAP PEMBANGUNAN EKOWISATA BOON PRING ANDEMAN DI DESA SANANKERTO, KECAMATAN TUREN, KABUPATEN MALANG, JAWA TIMUR: Indonesia - Ammar Iskandar Zulkarnain; Kornitasari, Yenny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The role of village fund on ecotourism development Boon Pring Andeman in the Sanankerto District Turen Malang East Java tries to explain in the paper comprehensively. Thus, it can be identified the role of village fund for ecotourism allocation and its contribution to PADes in the Sanankerto village. This research is using the village development theory, agency, the externality, stated in UU No. 6 Tahun 2014 as the relevancy of implementation village fund and the previous study of the paper. The research model is descriptive analytics with the collecting data method through interview and documentation through unit analysis which Director of BUMDes Kertoraharjo and Head village of Sanankerto. Furthermore, the analysis technique is using descriptive statistic following by triangulation method to test the validation of the data. The result of the research is the role of village fund in the Sanankerto village affects widely in villagers that shows in increasing economically including the work place opportunities following the reduction number of unemployment through ecotourism Boong Pring Anderman. The management of Boong Pring Andermans involved stakeholders in the Sanankerto village as the proves of planning and implication tourist destination